A Compact Gel Membrane Based on a Blend of PEO and PVDF for Dendrite‐Free Lithium Metal Anodes. Issue 21 (15th October 2019) - Liang, Shishuo; Shi, Yi; Ma, Tianyi; Yan, Wenqi; Qin, Sainan; Wang, Yuqi; Zhu, Yusong; Wang, Hongwei; Wu, Yuping
Abstract: A compact gel membrane (GM) with certain flexibility is facilely fabricated after a casted PEO/PVDF blend film is swelled by a LiPF6 ‐based liquid electrolyte. The GM exhibits a suitable lithium ionic conductivity (0.28 mS cm −1 at r.t., room temperature), a remarkable lithium‐ion transference number (0.52 at r.t.), and high mechanical strength (19.0 MPa) in dry or wet state. Owing to the special comprehensive performance of the GM, dendrite‐free reversible lithium plating/stripping (up to 500 h) at a current density of 0.5 mA cm −2 and a capacity of 0.25 mAh cm −2 is achieved for Li metal anodes at r.t.. The suppression of lithium dendrite of the obtained GM is further demonstrated in Li/GM/LiFePO4 cells with a high discharge capacity (142 mAh g −1 at r.t. and 160 mAh g −1 at 50 °C) and a superior cycling stability. This research provides a new strategy for developing lithium metal batteries with high stability and long cycle life. Abstract : Dendrite‐free : A compact PEO/PVDF‐based gel membrane preventing the growth of lithium dendrites thanks to its compact structure, good flexibility, strong mechanical strength before or after gelation, suitable ionic conductivity, high lithium‐ion transference number, and good interface contact with electrodes.